POLITENESS STRATEGIES USED BY TEACHERS IN ENGLISH CLASSROOMS - Irsa Irvista Rambe; Indra Hartoyo (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2020)
This study investigates the types of politeness strategy used by the teachers in classrooms interaction and how the politeness strategies were realized in classrooms interaction. The subjects in this study were teachers who used politeness strategies. This study used a descriptive qualitative design. The data were collected using the following instruments: observation, recording, field notes and interviews. The results of this study reveal that: (1) There are four politeness strategies found during the teaching and learning process used by English teachers, namely: Bald on Record, Positive Politeness, Negative Politeness and Off Record. (2) The dominant type used by English teachers at SMA YPK Medan is the Bald on Record Strategy, specifically Bald on Record was used 11 times by 2 English teachers at SMA YPK Medan and for reasons why the politeness strategy is used by the teacher English at SMA YPK Medan during the teaching and learning process illustrates that politeness is the best sentence, soft and polite. And it is very important to apply in the classroom because it will make it easier for teachers to teach students and make them respect each other. Furthermore, this strategy was successfully applied in the classroom during the learning process to get to know the character of students well.